2019
DOI: 10.1016/j.outlook.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric oncology nurses’ perceptions of prognosis-related communication

Abstract: Background: Disclosure of prognosis-related information is an essential aspect of communication with pediatric patients with cancer and their families. The nurse is believed to play an important role in this process, but nurse perceptions and experiences have not been well-described. Purpose: Provide an exploration of pediatric oncology nurses’ experiences with prognosis-related communication (PRC). Method: Mixed-methods, multi-phase design. This paper highlights the qualitative portion of the study. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 29 publications
1
23
0
6
Order By: Relevance
“…Similar feelings were reported in previous studies . Nurses in our study reported that a lack of collaboration between physicians and nurses forced them to work uninformed; they did not know what information had been conveyed to patients, which made them feel distressed.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Similar feelings were reported in previous studies . Nurses in our study reported that a lack of collaboration between physicians and nurses forced them to work uninformed; they did not know what information had been conveyed to patients, which made them feel distressed.…”
Section: Resultssupporting
confidence: 86%
“…In Newman's study, the researchers thought that nurses needed to educate and demonstrate to their physician colleagues the value and benefit that could be achieved from collaborative partnerships with nurses in disclosure and nurses playing a more prominent role in disclosure …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses are often excluded from the disclosure process and at times are explicitly instructed not to discuss prognosis with patients. 22 This exclusion can decrease the ability of nurses to fully support their patients and can lead to mixed messages that confuse or frustrate families. 22,23 This current individual-based model of prognostic disclosure lacks redundancy and creates a communication bottleneck.…”
mentioning
confidence: 99%